2022
DOI: 10.1002/app.53167
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of flame‐retardant rigid polyurethane foam with bio‐based phosphorus‐containing polyols and expandable graphite

Abstract: In the last decades, rigid polyurethane foam has focused on increasing renewable components and enhancing flame retardancy due to sustainable development and fire safety requirements. Herein, we report a bio‐based phosphorus‐containing polyester polyol (PMCP) that is synthesized with dimethyl methylphosphonate, malic acid, citric acid, and 1,6‐hexanediol in one pot. The hydroxyl value of PMCP is 485 ~ 512 mg KOH/g. As a result, it can be used as the sole polyol in the production of RPUF. Moreover, expandable g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…As well as other carbon-based nanomaterials, EG is usually applied as and AFR in combination with other FRs, which leads to remarkable improvement of the overall fire retardant properties of nanocomposite PUFs [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 ]. Recently, the influence of EG particle size on fireproof properties has been investigated [ 117 , 118 ].…”
Section: Carbon Nanomaterials As Fire Retardantsmentioning
confidence: 99%
“…As well as other carbon-based nanomaterials, EG is usually applied as and AFR in combination with other FRs, which leads to remarkable improvement of the overall fire retardant properties of nanocomposite PUFs [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 ]. Recently, the influence of EG particle size on fireproof properties has been investigated [ 117 , 118 ].…”
Section: Carbon Nanomaterials As Fire Retardantsmentioning
confidence: 99%
“…The addition amount reached to 10 php (about 6.3wt%), and the tensile strength and tear strength were correspondingly improved, and the flame retardant polyurethane foam could pass the vertical combustion test V-0 level. Yan Li et al [4] and Rao et al [5] synthesized phosphorus-containing long-chain diols with phenyl phosphonyl dichloride and ethylene glycol which was used to prepare flame retarded rigid polyurethane foam and polyurethane flexible foam respectively. The results showed that when the phosphorus content was 1.82%, the flame retardancy and mechanical properties of flame retardant PUF were improved simultaneously.…”
Section: Introductionmentioning
confidence: 99%